Effectiveness and cost-effectiveness of the PLAN-A intervention, a peer led physical activity program for adolescent girls: results of a cluster randomised controlled trial - Russell Jago; Byron Tibbitts; Kathryn Willis; Emily Sanderson; Rebecca Kandiyali; Tom Reid; Ruth R Kipping; Rona Campbell; Stephanie J MacNeill; William Hollingworth; Simon J. Sebire (BMC, 2021)
Abstract Background Physical activity is associated with improved health. Girls are less active than boys. Pilot work showed that a peer-led physical activity intervention called PLAN-A was a promising method of increasing physical activity in secondary school age girls. This study examined the effectiveness and cost-effectiveness of the PLAN-A intervention. Methods We conducted a cluster randomised controlled trial with Year 9 (13-14 year old) girls recruited from 20 secondary schools. Schools were randomly assigned to the PLAN-A intervention or a non-intervention control group after baseline data collection. Girls nominated students to be peer leaders. The top 18 % of girls nominated by their peers in intervention schools received three days of training designed to prepare them to support physical activity. Data were collected at two time points, baseline (T0) and 5-6 months post-intervention (T1). Participants wore an accelerometer for seven days to assess the primary outcome of mean weekday minutes of moderate-to-vigorous physical activity (MVPA). Multivariable mixed effects linear regression was used to estimate differences in the primary outcome between the two arms on an Intention-to-Treat (ITT) basis. Resource use and quality of life were measured and a within trial economic evaluation from a public sector perspective was conducted. Results A total of 1558 girls were recruited to the study. At T0, girls in both arms engaged in an average of 51 min of MVPA per weekday. The adjusted mean difference in weekday MVPA at T1 was − 2.84 min per day (95 % CI = -5.94 to 0.25) indicating a slightly larger decline in weekday MVPA in the intervention group. Results were broadly consistent when repeated using a multiple imputation approach and for pre-specified secondary outcomes and sub-groups. The mean cost of the PLAN-A intervention was £2817 per school, equivalent to £31 per girl. Economic analyses indicated that PLAN-A did not lead to demonstrable cost-effectiveness in terms of cost per unit change in QALY. Conclusions This study has shown that the PLAN-A intervention did not result in higher levels of weekday MVPA or associated secondary outcomes among Year 9 girls. The PLAN-A intervention should not be disseminated as a public health strategy. Trial registration ISRCTN14539759 -31 May, 2018.